2D- and 3D-QSAR, molecular docking, and virtual screening of pyrido[2,3-d]pyrimidin-7-one-based CDK4 inhibitors - Omar Husham Ahmed Al-Attraqchi, Mohd Nizam Mordi (Journal of Applied Pharmaceutical Science, 2021)
Cyclin-dependent kinases (CDKs) are important targets for combating various types of cancer. Inhibitors of the CDK4 enzyme are promising agents for clinical use as anticancer agents. In this study, structure-based and ligand-based drug design methods were applied on a dataset of 52 pyrido[2,3-d]pyrimidin-7-one-based CDK4 inhibitors. Predictive 2D- and 3D-quantitative structure-activity relationship (QSAR) models were developed and were analyzed for understanding the important molecular properties that affect the activity. Molecular docking was conducted to analyze the binding interactions between the ligands and the target enzyme. Also, virtual screening of the ChEMBL database was carried out using the validated QSAR model and the molecular docking procedure. A total of six compounds were identified as potentially novel CDK4 inhibitors that have favorable drug-like properties and can serve as lead compounds for the development of anticancer therapeutic agents.
Keywords: CDK4 inhibitors, QSAR, molecular docking, virtual screening